(untitled) (Tribhuvan University Journal of Microbiology, 2024)
Objectives: This study aimed to determine the prevalence of biofilm formation, assess the inhibitiory action of EDTA on biofilm production and to asses the antimicrobial resistance profiles of Escherichia coli from clinical samples. Methods: A descriptive study was conducted at Microbiology Department of Modern Technical College, Sanepa, Lalitpur. A total of 300 E. coli isolated from different clinical specimens were included in the study for biofilm formation by Tissue Culture Plate (TCP) method and inhibition by EDTA solution. Antimicrobial susceptibility testing was performed using the Kirby-Bauer disc diffusion method on Mueller Hinton agar according to CLSI guidelines. Results: Among the 300 E. coli isolates, 130 (43.3%) were found to be biofilm producers. Biofilm-producing E. coli showed significantly (p < 0.05) higher resistance to several antibiotics, including Amoxicillin (98.5%), Cefalexin (91.5%), Co-trimoxazole (87.7%), Cefixime (86.2%), Ceftriaxone (83.1%), Ciprofloxacin (73.8%), and Ofloxacin (73.8%). However, lesser drug resistance was observed among non-biofilm-producing E. coli. EDTA at concentrations of 5 mM and 10 mM greatly inhibited and reduced biofilm formation. Conclusion: Among the isolated E. coli, 43.3 % were biofilm producer and those strains exhibited higher antimicrobial resistance compared to non-biofilm producers. EDTA was found to be effective in inhibiting biofilm formation. Hence, EDTA can act as antibiofilm agent to control and minimize biofilm asssociated bacterial infections.